(untitled) (Cambridge, England, 2017)
MINDSET, the multi-level course from the organisation that produces the IELTS test, develops students' English skills and leaves them fully prepared for test day. MINDSET from Cambridge gets you inside the IELTS test with a unique blend of print and online content. Topic-based units organised by skill make it easy to find what you want. Designed for students currently at level A2, this Student's Book Foundation starts you on your IELTS journey with activities to help you develop your English skills and understand how the IELTS test works.
Keywords: Tiếng Anh,English language; Kỳ thi, câu hỏi,vv..,Examinations, questions, etc